1996
DOI: 10.1016/s0022-5223(96)70109-5
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral protection during moderate hypothermic circulatory arrest: Histopathology and magnetic resonance spectroscopy of brain energetics and intracellular pH in pigs

Abstract: The study shows that moderate hypothermic circulatory arrest at 28 degrees C with antegrade brain perfusion during circulatory arrest protects the brain but that retrograde cerebral perfusion at 28 degrees C does not protect the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…Mortality was 14.6% for DHCA patients, and 9.2% for MHCA patients (p [ 0. 17). There was no significant difference in stroke, temporary neurologic dysfunction, or dialysis-dependent renal failure.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Mortality was 14.6% for DHCA patients, and 9.2% for MHCA patients (p [ 0. 17). There was no significant difference in stroke, temporary neurologic dysfunction, or dialysis-dependent renal failure.…”
mentioning
confidence: 84%
“…However, the addition of uSACP changes the concept of HCA from total body circulatory arrest to lower body circulatory arrest, as the brain, upper extremities, and the spinal cord (through collateral circulation) are perfused with 16 C blood at a rate of 10 mL $ kg À1 $ min À1 . In animal models of HCA, ACP has been shown to maintain near normal cerebral metabolism, preserve cell structure, lower intracranial pressure, reduce cerebral edema, and reduce tissue acidosis [15][16][17]. These data may explain why the addition of ACP to DHCA has been shown to reduce the risk of TND, compared with DHCA plus retrograde cerebral perfusion or DHCA alone in several series of elective and emergent aortic arch replacement [18][19][20].…”
Section: Commentmentioning
confidence: 99%
“…For the population of newborn and juvenile patients, however, only few data exist regarding the application of ASCP (2,3). Moreover, retrospective human studies (4–6) and juvenile animal experiments (7) gave evidence that ASCP with more moderate temperatures such as 24–30°C instead of deep hypothermia of 18°C might be safe with regard to cerebral protection and maintenance of tissue energy metabolite levels, respectively. Because in the population of newborn and juvenile patients the risk of cerebral embolization as a result of atherosclerotic plaques is relatively low, prevention of cerebral ischemia plays the pivotal role in the management of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…The pigs who underwent DHCA+RCP or DHCA alone demonstrated a significant drop in cerebral pH during the protocol (39). In a separate study using the same model, these same investigators demonstrated preserved cell structure upon histopathologic analysis with HCA+ACP compared to HCA+RCP (40) The Mount Sinai group under Dr. Griepp has performed extensive laboratory work on the topic of ACP. These investigators determined that hypothermic SACP at 10˚-15˚C provides better cerebral protection than SACP at 20-25˚C based upon post-op behavioral scores in a chronic porcine circulatory arrest model (41).…”
Section: Antegrade Cerebral Perfusionmentioning
confidence: 98%